214. Predictability models for waiting time for radiotherapy treatment. (December 2018) - Rao, M.; Strolin, S.; Ungania, S.; Bruzzaniti, V.; Sanguineti, G.; Strigari, L.
Abstract : Purpose: This work deal with the waiting time that patient that receive radiotherapy treatments pass in the queue[1], in order to organize treatment processes effectively and efficiently and to ensure both the patient health and to facilities work optimization[2, 3] . Methods: Data belong to patients undergoing radiotherapy related to an observation period of 2 years were extrapolated from the record and verified system and classified into 8 macro categories. A simulation on the waiting time estimation was performed for all patients in the dataset. Our system considers: a priority assignment system coded by our institute staff; a characterization of machines and of their operation and maintenance; the historical data about patients and treatments; some different methods for calculating waiting time. Have been tested: a deterministic model, a Hidden Markov Model (HMM) to estimate the component not explained by the above parameters and a model based on a Support Vector Machine (SVM). Results: The first results demonstrate an average accuracy (forecast – real waiting time, measured on historical data) around 5–10 days. Conclusions: The implications of waiting list for radiotherapy treatment include perceived lower cancer control rates and patient suffering. The model represents a tool for effectively managing the capacity in a radiotherapy department to optimize the waiting lists for treatment.